DARI HAMEMAYU HAYUNING BAWANA KE KEADILAN SOSIAL: JEJAK NILAI JAWA DALAM PANCASILA DAN KONSTITUSI - Siti Fatimah; Azahery Insan Kamil; Nuruzzaman Nuruzzaman (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2026)
The discourse on social justice in Indonesia cannot be separated from the philosophical foundations of Pancasila and the cultural wisdom embedded in local traditions. One of the key philosophical values in Javanese tradition is Hamemayu Hayuning Bawana, which emphasizes the importance of maintaining harmony, balance, and collective well-being. Although it has long been practiced in local communities, its connection to constitutional principles (particularly the fifth principle of Pancasila) has not yet been extensively studied. This article poses two main questions: how can “Hamemayu Hayuning Bawana” be conceptualized as a source of values in the interpretation of the Indonesian Constitution, and to what extent does this value contribute to the understanding of social justice within the framework of Pancasila and the 1945 Constitution of the Republic of Indonesia. This study aims to examine the contribution of Hamemayu Hayuning Bawana as a philosophical concept in the legal interpretation of social justice. The research method employed is normative legal research using conceptual, philosophical, and comparative legal approaches. Primary and secondary legal materials were analyzed through qualitative interpretation, including the 1945 Constitution, relevant legislation, and the constitutions of several comparative countries. This study draws on the experiences of South Africa and Bolivia, which have successfully integrated indigenous values and customary law into their national constitutional systems. The research findings indicate that Hamemayu Hayuning Bawana can be understood as a source of constitutional values through the approaches of the “living constitution,” “sociological jurisprudence,” and “responsive law,” thereby contributing to the strengthening of substantive social justice. The integration of local values into constitutional interpretation has been shown to enhance the responsiveness of the law to the diverse social realities of society, while also providing an epistemological foundation for the decolonization of law by repositioning local wisdom within the national legal discourse. Therefore, this article recommends a contextual and culturally rooted constitutional approach. Keywords: Pancasila; Social Justice; Hamemayu Hayuning Bawana; Constitutionalism; Legal Decolonization.